Health-related quality of life of individuals on a weight loss program (Research, Society and Development, 2022)
Objective: To assess the health-related quality of life of patients before and after their participation in a weight loss program. Method: observational and comparative study, whose sample was non-probabilistic for convenience, consisting of 35 patients treated at an endocrinology service of a public university in Sergipe. Data collection was performed before and after the inclusion of participants in a weight reduction program using a sociodemographic questionnaire and the Impact of Weight on Quality of Life-Lite (IWQOL-Lite). Results: there was a predominance of females (91.4%); mean age 42 years; non-white skin color (71.4%); low education (57.1%) and low income (97.1%). The most frequent comorbidity was systemic arterial hypertension (72.4%). Weight reduction and BMI were correlated with the domains physical function, sex life, work and difficulties in public places. Conclusion: Patients in the program achieved weight reduction; increase in physical function, sex life, work capacity and reduction of difficulties in public places, achieving improved quality of life.